RANCANG BANGUN DAN ANALISA ALAT BANTU ERECTION BLOCK KAPAL MENGGUNAKAN THRUST BALL BEARING DI PT. KARIMUN SEMBAWANG SHIPYARD - Masirawan; Trisno Susilo; Edi kurniawan (Fakultas Sains dan Teknologi Universitas Karimun, 2020)
The high demand for building the vessels and ojfshore structure as jackup, such as platform, and submersible rig causing shipbuilding industry demanded to do some inovivation in order to make the ship building process to be more e'mzctive and e17icient. One of the key przocess on ship building is Block's Erection. This research carried out to include the design and analysis to create a tool fbr block erection which capable to boost the e17‘ectiveness and e17iciency on production of shipbuilding. The angular contact ball bearing is the Tool which created and proven very e,0‘ective to use on the process of erection block ship DRU 3 PT. Karimun Sembawang Shipyard. The research is applying descriftive analytic methode which use to analyse the compressive stress and shear strength and proved capable to receive the maximum load as planned. By using material grade AH 36 with tensile strength up to 285.000 Psi, proven much higher than total load applied to them. The results of the study showed that the Angular contact ball bearing capable to work on big load and also can move in all directions with will boost process the ship production significantly. Shipyard should be consider to develop the thrust ball bearing technology as a tool for block erection process.